Amir's Anxiety and Motive in Khaled Hosseini's The Kite Runner - Ajeng Pancar Tamara; Muhammad Rifqi (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2020)
This paper discusses Amir’s anxiety and motive in Khaled Hosseini’s “The Kite Runner". The library research method was applied in this research. In analyzing the data, the structural approach was used to scrutinize the intrinsic elements such as character, conflict, setting, and plot, while the psychological approach was used to examine extrinsic elements such as anxiety and motive of Amir as the main character in “The Kite Runner”. The results show that Amir, as the main character, is a caring, inferior, coward, optimistic, anxious, selfish, careless, sly, and patient person. It also indicates that Amir is a round static character since he has complex traits but his character as a caring person remains the same from the beginning to the end of the story. Besides, as the main character, Amir experienced both internal and external conflicts. The settings of time, social, and place showed the period in Afghanistan between 1975 and 2001 and the social stratum, Pashtun and Hazara in Kabul.  Dealing with the plot, it starts from Amir’s effort to get Baba’s recognition and respect, Amir’s anxiety after betraying Hassan, Amir efforts to take Sohrab out from Kabul, the liberation of Sohrab from Assef, the Sohrab suicide trial, up to Amir’s effort to get back Sohrab trust. Also, Amir’s anxiety deals with realistic, neurotic, and moral anxiety, while the motives are safety and security need, belongingness and love need, and self-esteem needs.